The influence of Information Quality, Service Quality, and Customer Experience On Customer Trust at PT PLN (Persero) ULP Klaten Kota - Bunga - Pertiwi; Rara Ririn Budi Utaminingtyas; Taviyastuti - Taviyastuti (Politeknik Negeri Semarang, 2020)
The development of technology and information can be used by a company to build the customer trust. A customer trust is needed to make long term relationship between customer and a company. This research is implemented to know the influence of Information Quality, Service Quality, and Customer Experience On Customer Trust at PT PLN (Persero) ULP Klaten Kota by knowing the partial and simultaneous influence of information quality, service quality and customer experience toward customer trust at PT PLN (Persero) ULP Klaten Kota. The data used in this research is primary data taken by interviewing the manager of PT PLN (Persero) ULP Klaten Kota and customer questionnaires. The sample in this research is 100 customers of PT PLN (Persero) ULP Klaten Kota. The Sampling technique used is purposive sampling and insidental sampling. The sata analysis model used is multiple linear regression analysis. The result of coefficient determination showed that 82,3% of customer trust is influenced by information quality, service quality and customer experience. While, the other is influenced by a other factors which are not examined in this research. The hypothesis result showed that information quality doesn't have a significant effect toward customer trust partially, service quality has significant effect toward customer trust and customer experience has a significant effect toward customer trust. Information quality, service quality and customer experience have a significant effect toward customer trust simultaneously